Integrasi pendidikan islam dan sains dalam pandangan Muhammad Naquib Al Attas - Mujiburrohman; M. Erlin Susri (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research is within the framework of religion and science in religion. Science and religion are often considered contradictory. Science comes from empirical practice, religion comes from religious revelations. The character Nuqoib al Attas in chapter 20 tries to find a correlation between science and religion. Nuqoib al Attas succeeded in combining science and religion, both in concept and in real practice. This research seeks to find the methodological thinking of Nuqoib al Attas in terms of science and religion. This research is classified as library research with the main material being texts about Naquib al Attas. Data analysis uses ethnography with a cultural background of the text. Conclusions come from the texts produced from the discovered manuscripts. The research results show that according to Naquib, science and religion are interconnected. It can be concluded that according to Naquib, Islamic knowledge, Islamic science is science based on divine values, with a collaboration between God's text-based revelation (Al-Quran) and God's verses in the form of nature.